(untitled) (Povijesni prilozi (Historical Contributions), 2019)
This article analyses one of the most important legal documents in the history of the Military Frontier in the 18th century, primarily from the social and legal point of view. The document in question was a medium of centralisation and legal modernisation carried out at the time by the court in Vienna.